Analsis Perbandingan Rekrutmen Aparatur Sipil Negara (ASN) : Di Malaysia Dan Di Indonesia - Amirtha, Indah Maysa; Dompak, Timbul; Lodan, Karol Teovani (LPPM Universitas Putera Batam, 2024)
Abstrak ditulis dalam bahasa Inggris, berisi uraian secara singkat pendahuluan, tujuan penelitian, metode, hasil dan kesimpulan. Abstrak ditulis dalam format satu kolom. 200-250 kata. Rata kiri kanan (justify The purpose of this study is to analyze and compare the recruitment process of the State Civil Apparatus (ASN) in Malaysia and Indonesia. Both countries have comprehensive ASN recruitment systems, but there are differences in terms of the mechanisms, selection criteria, and regulations followed. In Malaysia, the recruitment process is overseen by the Public Service Commission (PSC), which ensures that candidates are selected on merit through administrative selection procedures, written exams, interviews, and entry-level courses. However, in Indonesia, the National Civil Service Agency (BKN) oversees the recruitment process, which includes administrative selection, basic competency test (TKD), special competency test (TKB), and work experience, with guidelines set by the Minister of Administrative Reform and Bureaucratic Reform Regulation (PermenPAN-RB).The study findings show that although both countries have merit-based selection criteria, Malaysia places more emphasis on work performance and educational qualifications, while Indonesia places more emphasis on CPNS test results. Both countries also face challenges such as corruption, nepotism, and administrative control; however, Malaysia's governance mechanism has become more organized and efficient. On the other hand, administrative procedures in Indonesia are often slow, reducing recruitment efficiency.